A feasibility study on PLAY - Briones, Ralph Carlo E.; Castaneda, Charmaine F.; Castillo, Joyce S.; Dela Cruz, Tazha Rachel T.
PLAY is a new company that will provide a good quality of entertainment services to its customers. The establishment, whose core is to provide groups of friends a venue for their bonding activities, is in the form of rooms that can be rented on 3-hour intervals. PLAY will target teens and young professionals with ages 15 to 35 from social class A and B who live, work or study in the Metro Manila. PLAY will be providing their market of a wide array of services which includes: console gaming, karaoke TV, movie screening of DVDs, board games, free WiFi services and food. A distinctive characteristic of the service is the customer participation and the simultaneity of the various services. The company's awareness of the increasing demand for entertainment services like PLAY by the social class targets will remain invaluable. Presently, the need for entertainment establishments that promotes in high variety of activities is apparent and has become increasingly large. PLAY will differentiate its company in the marketplace in 2 specific ways; product differentiation towards a high variety of services and low but competitive pricing. These two factors will be the company's means of winning and retaining its potential customers. PLAY'S sales strategy is three tiered. First, the company will plan on capturing its potential market on first year through massive marketing campaigns that will promote product awareness causing a year-end gross sales of Php l5,357,000.00. Second, the company will plan to retain the current level of sales equal to or better than Php 15,386,000 in year two and Php 15,416,000 in year three. Thirdly, the company plans to aggressively promote its services with higher profit margins to allow for maximized profits. In its first year of operations, PLAY plans on gaining Php 946,000 of revenue. In years two through five the company will become more profitable as the marketing expenses are lessened and as the revenues are less affected by investment expenditures from year 1. In order to properly fund the start up of PLAY, the proprietors will avail of a Revolving Promissory Note Credit Line that will allow them to provide for working capital as needed with interest rates being charged only on amounts drawn against the line. The initial start up expense for PLAY is Php 4,086,615.00 which include: capital funds to be used for the establishment and building improvements, service equipment, professional fees, marketing costs and cost of leasing. Wherein, marketing funds will be used for various print materials and advertisements.